2020
DOI: 10.3390/jcm9103109
|View full text |Cite
|
Sign up to set email alerts
|

Environment and Lifestyle: Their Influence on the Risk of RA

Abstract: Background: Rheumatoid arthritis (RA) is a complex disease in which environmental agents are thought to interact with genetic factors that lead to triggering of autoimmunity. Methods: We reviewed environmental, hormonal, and dietary factors that have been suggested to be associated with the risk of RA. Results: Smoking is the most robust factor associated with the risk of RA, with a clear gene–environment interaction. Among other inhalants, silica may increase the risk of RA in men. There is less evidence for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 130 publications
0
18
0
Order By: Relevance
“…Single nucleotide polymorphism sites (SNPs) are randomly assigned at conception, bias from reverse causation, and residual confounding is avoided ( 22 ). Although observational studies found the association between coffee intake and bone health, such as bone mass index, fracture, rheumatoid arthritis, and osteoarthritis ( 12 , 23 , 24 ), data are limited for the relationship of genetically predicted habitual coffee intake concerning the bone disease. One MR analysis support that coffee intake is causally associated with an increased risk of OA ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Single nucleotide polymorphism sites (SNPs) are randomly assigned at conception, bias from reverse causation, and residual confounding is avoided ( 22 ). Although observational studies found the association between coffee intake and bone health, such as bone mass index, fracture, rheumatoid arthritis, and osteoarthritis ( 12 , 23 , 24 ), data are limited for the relationship of genetically predicted habitual coffee intake concerning the bone disease. One MR analysis support that coffee intake is causally associated with an increased risk of OA ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Third, although this study classified coffee consumption based on the number of cups of coffee consumed per day, cup size, strength, and concentration of coffee may vary considerably. Fourth, there has been no investigation of other foods that may affect the risk of RA, such as fish, fruit, vegetables, and tea [27]. Finally, the small number of RA patients in our study may not have revealed the significant relationship; thus, a larger-scale study is needed.…”
Section: Discussionmentioning
confidence: 86%
“…RA is an autoimmune disease mainly characterized by chronic inflammation of synovium, which can cause joint swelling and pain, and then lead to narrowing of joint space, destruction of cartilage, joint deformity, and finally different degrees of disability (Maden, 2020;Salliot et al, 2020). According to statistics, RA has been worldwide incidence, the average incidence rate is 1%, the prevalence rate of China is 0.3-0.4%.…”
Section: Discussionmentioning
confidence: 99%